2022
DOI: 10.3390/plants11060744
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Traditional and Modern Uses of Wild Edible Native Plants of Chile: Challenges and Future Perspectives

Abstract: Wild Edible Plants (WEPs) still play a vital role in the subsistence of many traditional communities, while they are receiving increasing recognition in tackling food security and nutrition at the international level. This paper reviews the use patterns of native WEPs in Chile and discusses their role as future crops and sources of food products. We conducted an extensive literature review by assessing their taxonomic diversity, life forms, consumption and preparation methods, types of use (traditional and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Many plant species in Chile have ethnobotanical and food value. León-Lobos et al [216] conducted a national review of reported edible plants and their manner of use. They reported that 330 (7.8%) of the nearly 4300 plant species in Chile were used as food, primarily by indigenous cultures.…”
Section: Vegetation and Ethnobotanymentioning
confidence: 99%
“…Many plant species in Chile have ethnobotanical and food value. León-Lobos et al [216] conducted a national review of reported edible plants and their manner of use. They reported that 330 (7.8%) of the nearly 4300 plant species in Chile were used as food, primarily by indigenous cultures.…”
Section: Vegetation and Ethnobotanymentioning
confidence: 99%
“…There are several classifications of plants, which depend on a specific categories such as higher and lower plants based on the existence of flowers or vascular system; common and unconventional edible plants; traditional and modern wild edible plants [101]; cultivated and wild edible plants [37], and conventional and unconventional food plants [102]. The common attributes that can be existed in edible mushrooms and edible plants are being consumable foods and having a nutritional value, such as desirable content of proteins, carbohydrates, or vitamins.…”
Section: Unconventional Foods Of Plants and Mushroomsmentioning
confidence: 99%
“…USO usage for food, medicine, dye and even as a pest poison is apparent across the Mediterranean Basin, but varies both at a regional and local scale (Biscotti et al 2018;Geraci et al 2018;Karous et al 2021;Korkmaz et al 2014;Tardío et al 2006). Despite significant cultural destruction, Mapuche people in Chile and Argentine Patagonia (León-Lobos et al 2022;Ochoa and Ladio 2015) still use a small selection of USOs for food.…”
Section: Scale and Scope Of Human Uso Interactions In Mediterranean-t...mentioning
confidence: 99%
“…In the Greater Cape, such taxa would include members of the Dioscoraceae and Iridaceae (Archer 1994;van Wyk and Gericke 2000), in California the Liliaceae and Asparagaceae (Anderson 2005), while Tardío et al (2006) report that Glycyrhiza glabra (Fabaceae) is frequently targeted in the Mediterranean Basin. Species of Oxalidaceae, Santalaceae and Apiaceae are important in Patagonia (Ochoa and Ladio 2015), while in Chile, Alstroemeriaceae, Apiaceae, Asteraceae, and Dioscoreaceae are key taxa (León-Lobos et al 2022).…”
Section: Patterns Of Uso Harvestmentioning
confidence: 99%